Interactions of hyaluronan grafted on protein surfaces studied using a quartz crystal microbalance and a surface force balance. Issue 37 (7th October 2015) - Jiang, Lei; Han, Juan; Yang, Limin; Ma, Hongchao; Huang, Bo
<x xml:space="preserve">Abstract</x> A simple layer-structured model is set up to mimic the structure of the vocal fold. The physical mechanism of hyaluronan in the vocal fold is investigated.